The Long and Winding Road: Recent Directions in Medicaid & SCHIP - Milligan, Charles J. Jr. (The Hilltop Institute, 2008)
The Center’s Executive Director Chuck Milligan and Director of Acute Care Policy Ann Volpel participated in separate panel discussions at the National Meeting for State Coverage Initiatives that was held February 6-8, 2008 in Nashville, Tennessee. Milligan participated on a panel addressing emerging issues in the Medicaid and SCHIP programs and gave a presentation on recent directions in broad national policy, their implications for states, trends in state activities, and reforms approved by CMS under the Deficit Reduction Act and Section 1115 Waiver programs.
Keywords: Medicaid; SCHIP; Medicare, Medicaid and SCHIP Extension Act of 2007